Studies on Synthesis and Dyeing Performance of Some Fluorescent Brightening Agents Based on Stilbene Derivatives - Patel, P.S.; Patel, S.K.; Patel, K.C. (Asian Journal of Chemistry, 2010)
Various fluorescent brightening agents have been synthesised by condensing 4,4´-diaminostilbene-2,2´-disulphonic acid with cyanuric chloride, N-benzyl aniline and various amines. They are characterised by their nitrogen elemental analysis, UV-visible spectra, IR and PMR spectra. Their dyeing performance has been assessed on polyester and nylon fabric to show very good to excellent wash fastness and good to very good light fastness properties.